CD19+CD1dhiCD5hi B Cells Can Downregulate Malaria ITV Protection by IL-10 Secretion - Guan, Hongli; Peng, Jiacong; Jiang, Liping; Mo, Gang; Li, Xiang; Peng, Xiaohong (Frontiers in Public Health, 2020)
Infection treatment vaccine (ITV) can lead to sterile protection against malaria infection in mice and humans. However, parasite breakthrough is frequently observed post-challenge. The mechanism of rapid decline in protection after the last immunization is unclear. Herein, C57BL/6 mice were immunized with 103, 105, or 107 ITV thice at 14-day intervals. Mice were challenged with 103 parasites at 1, 3, and 6 months after last immunization and the protection was checked using blood smear. The phenotypes of B cells were analyzed by flow cytometry. The levels of serum cytokines were quantified using cytometric bead array. The 103 ITV vaccination group exhibited 100% protection at 1 month after last immunization, and the 105 group showed sterile protection at 3 months after last immunization. However, the 107 group showed only partial protection. Further, the protection declined to 16.7% at 6 months after last immunization in 105 and 107 groups, whereas it maintained for more than 60% in 103 group. The number of memory B cells (MBC) decreased along with the decline in protection. However, programmed cell death protein 1 (PD-1) expressed on MBCs did not show significant variation among the three groups. Interestingly, CD19+CD1dhiCD5hi B cells, defined as B10 cells, exhibited negative regulation with respect to protection. The numbers of CD19+CD1dhiCD5hi B cells in the 103 group at 1 months and in the 105 group at 3 months post-immunization were the lowest compared to those in the other groups. Moreover, the serum levels of interleukin 10 (IL-10) in these two groups were also significantly lower than those in other groups. We conclude that higher immunization dose may not lead to better protection with the malaria vaccine as CD19+CD1dhiCD5hi B cells can downregulate ITV protection against malaria via IL-10 secretion. These results could facilitate the design of an effective long-lasting malaria vaccine with the aim of maintaining MBC function.